A origem social da enfermeira padrão: o recrutamento e a imagem pública da enfermeira no Brasil, 1920-1960 - Luiz Otávio Ferreira (Centre de Recherches sur les Mondes Américains, 2019)
The objective of the article is to analyze social origin – social class, gender, race and schooling – of the nurses graduated in the most important school of Brazilian nurses of the first half of the 20th century, Ana Nery Nursing School (EEAN). What is the social origin of the women who attended the nurses’ school during the process of institutionalization of the profession that lasted from 1923 to 1961? Was the social origin of the nurse a decisive factor for the organization and the social and scientific legitimation of nursing? Was the public image of the profession related to the social background of nurses?